Bionic diamond and preparation method and application thereof
By treating highly directional pyrolytic graphite under high temperature and high pressure conditions, bionic diamond with layered interlocking structures is solved, and the problems of poor impact resistance and short service life caused by the brittleness of diamond materials are achieved, and the balance of high hardness and high toughness is achieved .
Patent Information
- Application Number
- CN202411348231.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-09-26
AI Technical Summary
Due to its brittleness, existing diamond materials have short service life and poor impact resistance, making it difficult to improve fracture toughness while maintaining high hardness.
By treating highly directional pyrolytic graphite under high temperature and high pressure conditions, bionic diamond with shell-like structure is formed, and the formation of a layered interlocking structure is achieved. The method includes high temperature and high pressure treatment under a pressure of 13-22 GPa and a temperature of 1400-2000°C, and controlling stress release during cooling.
It significantly improves the fracture toughness of the material while maintaining excellent hardness, overcoming the problems of poor impact resistance and short service life caused by the brittleness of traditional diamond materials.
Smart Images

Figure CN119455805A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of preparation of high-toughness and extremely hard materials, and in particular to a bionic diamond and a preparation method and application thereof. Background Art
[0002] In the field of nano-polycrystalline diamond (NPD) and its toughening technology, existing technologies generally face the dilemma of balancing hardness and toughness. Although diamond has extremely high hardness, its inherent brittleness limits its service life and performance in high-impact environments. Several existing technologies attempt to improve the toughening of diamond materials, but they all have different defects, because hardness and toughness are often contradictory in materials. Generally, the higher the hardness, the lower the toughness. A typical example is diamond, which has a Vickers hardness of 80 to 120 GPa. It is the hardest material in nature and has important uses in mineral mining, industrial manufacturing, and military fields. It is an important national strategic material. However, due to the strong covalent bond structure of diamond, its fracture toughness is only 4 to 6 MPa∙m 0.5 , poor impact resistance, which seriously reduces its cutting efficiency and service life.
[0003] In order to solve this problem, the existing technology usually adopts the method of introducing adhesives. For example, in the preparation of polycrystalline diamond (PCD), metal adhesives such as Ni, Co, Fe, etc. are often added and sintered under high pressure and high temperature conditions. Although this type of technology enhances the toughness of the material to a certain extent, it will significantly reduce its hardness (usually reduced to about 40 GPa), and the thermal expansion coefficient of the metal adhesive is quite different from that of diamond, which makes the material easy to fall off in a high temperature environment, significantly affecting the thermal stability and durability of PCD. In addition, although some studies have tried to replace metal adhesives with hard ceramics such as B4C or c-BN, their hardness still cannot reach the level of single crystal diamond (usually less than 80 GPa).
[0004] In addition, the development of nano-polycrystalline diamond (NPD) provides a new direction for improving the toughness of diamond. By introducing high-density grain boundaries, NPD changes the fracture mode of the material from transcrystalline to intercrystalline fracture. This change effectively improves the fracture toughness of the material, making the toughness of NPD about twice that of single-crystal diamond (K IC ≈ 8 MPa·m 0.5 ), and its hardness value has reached more than 120 GPa. However, despite the improvement in hardness and toughness of NPD, the inherent brittleness of diamond still exists, making its fracture toughness and impact resistance under extreme conditions unsatisfactory. This shows that the balance between hardness and toughness cannot be completely solved by adjusting the grain boundary density alone, and a more effective microstructure design is urgently needed.
[0005] Shells in nature provide inspiration for bionic design. The "brick + mud" structure of shells consists of alternating hard calcium carbonate layers and soft protein layers to form a multi-level interlocking structure. This structure gives the shells excellent hardness, toughness and impact resistance, and their toughness even far exceeds that of a single component material. Based on this bionic design concept, some studies in recent years have begun to apply shell structures to ceramics and composite materials, significantly improving the toughness of the materials. However, there are relatively few attempts in existing technologies to introduce this structure into diamond materials. In particular, how to further improve toughness under the premise of extremely high hardness is still an unresolved technical bottleneck. Summary of the invention
[0006] One of the technical problems to be solved by the present invention is how to improve the fracture toughness of nano-polycrystalline diamond (NPD) while maintaining high hardness, overcome the problems of short service life and poor impact resistance of traditional diamond materials due to brittleness, and provide a method for preparing bionic diamond with a shell-like structure.
[0007] The present invention provides a method for preparing a bionic diamond, comprising the following steps: S1: Preparation of highly oriented pyrolytic graphite as raw material for biomimetic diamond; S2: subjecting the highly oriented pyrolytic graphite to a high temperature and high pressure treatment at a preparation pressure of 13-22 GPa and a preparation temperature of 1400-2000°C; S3: Cooling the highly oriented pyrolytic graphite treated in step S2 to room temperature, and obtaining bionic diamond after pressure relief.
[0008] Compared with the prior art, the present invention has the following advantages: by processing highly oriented pyrolytic graphite under high temperature and high pressure conditions, the layered interlocking structure of bionic diamond is realized, which is similar to the alternating arrangement of calcium carbonate and protein in shells, and has extremely high hardness and excellent toughness. Compared with the existing nano polycrystalline diamond (NPD), the present invention significantly improves the fracture toughness of the material by precisely controlling pressure and temperature, while maintaining excellent hardness, overcoming the problems of poor impact resistance and short service life caused by the brittleness of traditional diamond materials; through the above technical scheme, a preparation method of bionic diamond in the present invention successfully solves the brittleness problem of traditional diamond materials, and at the same time achieves a balance between high hardness and high toughness of the material, so that it exhibits excellent performance in industrial applications.
[0009] In a possible implementation, in step S2, the conditions of the high temperature and high pressure treatment are: pressure P=15~22 GPa, temperature T=1400~2000°C, and insulation for 30 min.
[0010] By controlling the conditions of high temperature and high pressure treatment through the above possible implementation methods, the graphite material can be fully converted into diamond and form a stable layered structure, thereby effectively improving the hardness and toughness of the material.
[0011] In a possible implementation, in step S2, the conditions of the high temperature and high pressure treatment are: pressure P=13~15 GPa, T=1600~2000°C, and insulation for 30 min.
[0012] Through the above possible implementation methods, the conditions of high temperature and high pressure treatment are controlled. The pressure and temperature within this range are more suitable for forming the cross-interlocking structure of bionic diamond, further improving the impact resistance of the material while maintaining a high hardness.
[0013] In a possible implementation, in step S2, the heating method used for the high temperature and high pressure treatment is to wrap the highly oriented pyrolytic graphite with hexagonal boron nitride, heat it with a rhenium tube, and simultaneously measure the temperature with a tungsten-rhenium thermocouple.
[0014] Through the above possible implementation methods, the above specific heating method can achieve uniform temperature increase, ensure that the material is heated evenly, reduce the generation of local thermal stress, and ensure the structural integrity and performance stability of the bionic diamond.
[0015] In a possible implementation, in step S2, the high temperature and high pressure treatment is performed by pressurizing with a large cavity press.
[0016] Through the above possible implementation methods, the large cavity press can provide a more stable pressure environment, reduce the impact of pressure fluctuations on the material structure during the pressing process, and ensure that the diamond material can evenly form an ideal layered interlocking structure.
[0017] In a possible implementation, in step S3, the cooling rate of the highly oriented pyrolytic graphite is 90-110° C. / min.
[0018] Through the above possible implementation methods, a cooling rate of 90-110°C / min can effectively control the stress release inside the material, prevent the material structure from being damaged due to too fast or too slow cooling, and further improve the toughness and impact resistance of the material.
[0019] The second technical problem to be solved by the present invention is to provide a bionic diamond to solve the problem of short service life and poor impact resistance of conventional diamond materials due to brittleness.
[0020] In order to solve the above technical problems, the present invention provides a bionic diamond, which is prepared by the above preparation method.
[0021] In a possible implementation, the bionic diamond has a layered structure or a cross-interlocking layered structure.
[0022] This type of structure enables the bionic diamond to effectively disperse stress when subjected to high-intensity loads, thereby greatly improving its impact resistance and service life.
[0023] The third technical problem to be solved by the present invention is the application of the above-mentioned bionic diamond, which includes the application of the bionic diamond in industrial fine cutting and finishing.
[0024] Through the improved bionic diamond structure, it greatly improves the impact resistance while maintaining high hardness, making it particularly suitable for use in high-precision, high-strength industrial cutting and finishing fields, significantly improving processing quality and efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is the X-ray diffraction pattern of the bionic diamond prepared in Example 1; Figure 2 is a SEM image of the bionic diamond prepared in Example 1; Figure 3 is the X-ray diffraction pattern of the bionic diamond prepared in Example 2; Figure 4 is the indentation image of the bionic diamond prepared in Example 2; Figure 5 is a SEM image of the bionic diamond prepared in Example 2; Figure 6 is the X-ray diffraction pattern of the bionic diamond prepared in Example 3; Figure 7 is the indentation image of the bionic diamond prepared in Example 3; Figure 8 is a SEM image of the bionic diamond prepared in Example 3; Fig. 9 is a TEM image of the bionic diamond prepared in Example 3; Fig.10 is the X-ray diffraction pattern of the bionic diamond prepared in Example 4; Fig.11 is the indentation image of the bionic diamond prepared in Example 4; Fig.12 is a SEM image of the bionic diamond prepared in Example 4; Fig.13 is the X-ray diffraction pattern of the bionic diamond prepared in Example 5; Fig.14 is the indentation image of the bionic diamond prepared in Example 5; Fig.15is a SEM image of the bionic diamond prepared in Example 5; Fig.16 is the X-ray diffraction pattern of the bionic diamond prepared in Example 6; Fig.17 is the indentation image of the bionic diamond prepared in Example 6; Fig.18 is a SEM image of the bionic diamond prepared in Example 6; Fig.19 is the X-ray diffraction pattern of the bionic diamond prepared in Example 7; Fig. 20 is the indentation image of the bionic diamond prepared in Example 7; Fig.21 is a SEM image of the bionic diamond prepared in Example 7; Fig. 22 is the X-ray diffraction pattern of the bionic diamond prepared in Example 8; Fig.23 is the indentation image of the bionic diamond prepared in Example 8; Fig.24 This is the SEM image of the bionic diamond prepared in Example 8. DETAILED DESCRIPTION
[0026] First, those skilled in the art should understand that these implementations are only used to explain the technical principles of the embodiments of the present application, and are not intended to limit the protection scope of the embodiments of the present application. Those skilled in the art can make adjustments to them as needed to adapt to specific application scenarios.
[0027] The present invention provides a method for preparing a bionic diamond, comprising the following steps: S1: Preparation of highly oriented pyrolytic graphite as raw material for biomimetic diamond; S2: subjecting the highly oriented pyrolytic graphite to a high temperature and high pressure treatment at a preparation pressure of 13-22 GPa and a preparation temperature of 1400-2000°C; S3: Cooling the highly oriented pyrolytic graphite treated in step S2 to room temperature, and obtaining bionic diamond after pressure relief.
[0028] As a preferred solution, in step S2, the conditions of the high temperature and high pressure treatment are: pressure P = 15 ~ 22GPa, temperature T = 1400 ~ 2000 ° C, and heat preservation for 30 minutes. The temperature and pressure range in this step not only helps the effective conversion of graphite into diamond, but also promotes the formation of a layered interlocking structure, so that the material exhibits better mechanical properties at the microscopic level.
[0029] As a preferred solution, in step S2, the conditions of the high temperature and high pressure treatment are: pressure P=13~15GPa, T=1600~2000℃, and heat preservation for 30 minutes. By regulating the temperature and pressure within this range, not only can the cross-interlocking structure of bionic diamond be achieved, but also its performance under high impact load can be enhanced.
[0030] As a preferred solution, in step S2, the high temperature and high pressure treatment adopts a heating method of wrapping the highly oriented pyrolytic graphite with hexagonal boron nitride, heating with a rhenium tube, and synchronously measuring the temperature with a tungsten-rhenium thermocouple. This heating method ensures that the sample is heated evenly, thereby reducing microstructural defects caused by uneven temperature and further improving the uniformity and strength of the prepared diamond.
[0031] As a preferred solution, in step S2, the high temperature and high pressure treatment is pressurized by a large cavity press. The use of a large cavity press can provide a more stable pressure environment, thereby reducing stress concentration of the material during processing and ensuring that the layered interlocking structure of the diamond can be effectively maintained and strengthened.
[0032] As a preferred solution, in step S3, the cooling rate of the highly oriented pyrolytic graphite is 90-110°C / min. Controlling the cooling rate helps to release the internal stress of the material reasonably, prevents the material structure from being damaged due to improper cooling, and further improves the toughness and impact resistance of the material.
[0033] The present invention also provides a bionic diamond, which is prepared by any one of the preparation methods of claims 1-6.
[0034] As a preferred solution, the bionic diamond has a layered structure or a cross-interlocked layered structure. The design of this structure is inspired by the structure of shells in nature. When subjected to external impact, it can effectively disperse energy through the slip and interaction between different layers to avoid brittle fracture caused by stress concentration. This structure can effectively disperse the externally applied stress, thereby significantly improving the impact resistance and service life of the material.
[0035] The present invention also provides an application of the bionic diamond, which includes application of the bionic diamond in industrial fine cutting and finishing.
[0036] The present application is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0037] Example 1 S1: Highly oriented pyrolytic graphite (20*20*1mm) is used as raw material and laser cut into cylindrical shape (2mm in diameter and 1mm in height); S2: The highly oriented pyrolytic graphite is wrapped with hexagonal boron nitride, heated by a rhenium tube, and the temperature is measured synchronously by a tungsten-rhenium thermocouple. A Kawai-type large-volume multi-stage anvil cell experimental device is used to prepare bionic diamond at a pressure of P = 13 GPa and a temperature of T = 1400 °C, and the holding time range is 30 min; S3: Slowly cool down to room temperature at a rate of 100 ℃ / min, and then release the pressure. The main components of the sample are graphite, hexagonal diamond and cubic diamond, and the morphology is a layered structure.
[0038] The X-ray diffraction results of the samples are shown in Figure 1 ; SEM images are shown in Figure 2 .
[0039] Example 2 Example 2 is similar to Example 1, and adopts the same experimental assembly, method and pressure conditions as Example 1 (pressure P=13 GPa). The graphite content in the bionic diamond is regulated by regulating the temperature, and the bionic diamond is prepared at a temperature of T=1600°C. As the synthesis temperature increases, the graphite content in the sample decreases. Its main components are graphite, hexagonal diamond and cubic diamond, and its morphology is a layered structure. Its hardness HV=130.0~139.4 GPa, (F=9.8 N), fracture toughness K IC =8.3~12.6MPa.m 0.5 XRD see Figure 3 , indentation diagram see Figure 4 , SEM images are shown in Figure 5 .
[0040] Example 3 Example 3 is similar to Example 1, and adopts the same experimental assembly, method and pressure conditions as Example 1 (pressure P=13 GPa). Bionic diamond was prepared at a temperature of T=1800°C. As the synthesis temperature continues to increase, the graphite content in the sample further decreases. XRD test shows that its main components are hexagonal diamond and cubic diamond. TEM test shows that trace graphite (thickness less than 10nm) is discontinuously distributed in the sample. SEM test morphology is a cross-interlocking layered structure similar to a shell. Its hardness HV=126.6~144.0GPa, (F=9.8 N), fracture toughness increases, K IC =14.8~20.2MPa.m 0.5 Its toughness is about 3 to 4 times that of single crystal diamond, and its shell-like microstructure effectively balances the contradiction between hardness and toughness in NPD.
[0041] XRD Figure 6 , indentation diagram see Figure 7 , SEM images are shown in Figure 8 , TEM image see Fig. 9, indicating that trace amounts of graphite (thickness less than 10 nm) are discontinuously distributed in the sample.
[0042] Example 4 Example 4 is similar to Example 1, using the same experimental assembly, method and pressure conditions (pressure P = 13 GPa) as Example 1. The bionic diamond was prepared at a temperature of T = 2000 °C. As the synthesis temperature increases, the sample does not contain graphite. Its main components are hexagonal diamond and cubic diamond, and the SEM test morphology is still a cross-interlocking layered structure. Its hardness HV = 126.6 ~ 139.7 GPa, (F = 9.8 N) is close to that of Example 3, and the fracture toughness is reduced by K IC =10.1~12.0 MPa.m 0.5 .
[0043] XRD Fig.10 , indentation diagram see Fig.11 , SEM images are shown in Fig.12 .
[0044] Example 5 Example 5 is similar to Example 1, using the same experimental assembly and method as Example 1, and the same temperature as Example 4 (T=2000 ℃). At a temperature of T=2000 ℃, the layered structure in the bionic diamond is regulated by regulating the synthesis pressure. Bionic diamond is prepared at a pressure of P=15GPa. As the synthesis pressure increases, the sample is still a composite phase of hexagonal diamond and cubic diamond, and SEM testing shows that the sample is a layered interlocking structure. Compared with Example 4, its hardness increases by HV=130.4~144.4GPa, (F=9.8 N), and the fracture toughness decreases by K IC =8.2~11.3 MPa.m 0.5 .
[0045] XRD Fig.13 , indentation diagram see Fig.14 , SEM images are shown in Fig.15 .
[0046] Example 6 Example 6 is similar to Example 1, using the same experimental assembly and method as Example 1, and the same temperature as Example 4 (T=2000 ℃). The synthesis pressure was increased to P=18GPa to prepare biomimetic diamond. As the synthesis pressure increased, the sample was still a composite phase of hexagonal diamond and cubic diamond. SEM testing showed that the layered structure of the sample was destroyed. Compared with Example 5, its hardness increased by HV=137.5~152.8 GPa, (F=9.8 N), and the fracture toughness decreased by K IC =7.5~10.3 MPa.m 0.5 .
[0047] XRD Fig.16 , indentation diagram see Fig.17 , SEM images are shown in Fig.18 .
[0048] Example 7 Example 7 is similar to Example 1, using the same experimental assembly and method as Example 1, and the same temperature as Example 4 (T=2000 ℃). The synthesis pressure was increased to P=20 GPa to prepare biomimetic diamond. As the synthesis pressure continued to increase, the sample was still a composite phase of hexagonal diamond and cubic diamond. SEM testing showed that the layered structure of the sample was further destroyed and granular. Compared with Example 6, its hardness continued to increase HV=142.1~159.1 GPa, (F=9.8 N), and the fracture toughness further decreased, K IC =7.2~9.1 MPa.m 0.5 .
[0049] XRD Fig.19 , indentation diagram see Fig. 20 , SEM images are shown in Fig.21 .
[0050] Example 8 Example 8 is similar to Example 1, using the same experimental assembly and method as Example 1, and the same temperature as Example 4 (T=2000 ℃). The synthesis pressure is continued to increase to P=22GPa to prepare bionic diamond. As the synthesis pressure increases, the sample is still a composite phase of hexagonal diamond and cubic diamond, and SEM test shows that the sample is nano-granular. Compared with Example 7, its hardness continues to increase HV=151.8~181.7 GPa, (F=9.8 N), and the fracture toughness is further reduced K IC =6.8~9.2MPa.m 0.5 .
[0051] XRD Fig. 22 , indentation diagram see Fig.23 , SEM images are shown in Fig.24 .
[0052] From the above embodiments, it can be found that the present invention uses highly oriented pyrolytic graphite as raw material, utilizes its high pressure bending and martensitic phase transformation, and can form a cross-interlocking layered structure by reasonably controlling the temperature and pressure of high temperature and high pressure treatment. Through a unique high temperature and high pressure method to regulate its microstructure and graphite content, a shell-like structure bionic diamond is prepared. Its hardness is higher than that of single crystal diamond (111) crystal plane, and its toughness is about 3 to 4 times that of single crystal, which effectively balances the contradiction between hardness and toughness in diamond.
[0053] It can be seen from the above embodiments that the bionic diamonds prepared by the preparation methods of Examples 3, 4, and 5 of the present invention all have a layered interlocking structure and a cross-interlocking layered structure, and the bionic diamonds prepared by controlling the pressure to P=13~15 GPa, T=1600~2000 ℃, and keeping warm for 30 min under high temperature and high pressure conditions all have this structure. Further, through the slip and interaction between different layers, effective energy dispersion is achieved to avoid brittle fracture caused by stress concentration. This structure can effectively disperse the externally applied stress, thereby significantly improving the impact resistance and service life of the material, and solving the problems existing in the background technology. Although the bionic diamonds prepared in other embodiments do not have the above structure, their strength and toughness have reached values above a level, further proving that the present invention solves the technical problems existing in the background technology through an improved preparation method.
[0054] The above are only preferred embodiments of the present invention. The embodiments within the range are not listed one by one. Without departing from the principle of this patent (using highly oriented pyrolytic graphite as raw material, regulating its layered structure by pressure, regulating the graphite content by temperature, and preparing bionic diamonds with a shell-like structure), improvements and embellishments should be included in the protection scope of the present invention.
[0055] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "in the present embodiment", "specific example", or "some examples" etc. means that the specific features, mechanisms, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, mechanisms, materials or characteristics described may be combined in a suitable manner in any one or more embodiments or examples. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0056] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.
Claims
1. A method for preparing bionic diamond, characterized in that: The following steps are involved: S1: Preparation of highly oriented pyrolytic graphite as raw material for biomimetic diamond; S2: subjecting the highly oriented pyrolytic graphite to a high temperature and high pressure treatment at a preparation pressure of 13-22 GPa and a preparation temperature of 1400-2000°C; S3: Cooling the highly oriented pyrolytic graphite treated in step S2 to room temperature, and obtaining bionic diamond after pressure relief.
2. The method for preparing biomimetic diamond according to claim 1, characterized in that: In step S2, the conditions of the high temperature and high pressure treatment are: pressure P=15~22 GPa, temperature T=1400~2000°C, and insulation time 30 min.
3. The method for preparing biomimetic diamond according to claim 1, characterized in that: In step S2, the conditions of the high temperature and high pressure treatment are: pressure P=13~15 GPa, T=1600~2000°C, and heat preservation for 30 min.
4. The method for preparing biomimetic diamond according to claim 1, characterized in that: In the step S2, the heating method adopted for the high temperature and high pressure treatment is to wrap the highly oriented pyrolytic graphite with hexagonal boron nitride, heat it with a rhenium tube, and measure the temperature synchronously with a tungsten-rhenium thermocouple.
5. The method for preparing biomimetic diamond according to claim 1, characterized in that: In the step S2, the pressurization method used in the high temperature and high pressure treatment is to pressurize using a large cavity press.
6. The method for preparing the bionic diamond according to claim 1 of the cooling requirement of highly oriented pyrolytic graphite, characterized in that: In the step S3, the cooling rate of the highly oriented pyrolytic graphite is 90-110° C. / min.
7. A bionic diamond, characterized in that: The bionic diamond is prepared by any one of the preparation methods of claims 1-6.
8. The biomimetic diamond according to claim 7, characterized in that: The bionic diamond has a layered structure and a cross-interlocked layered structure.
9. An application of the bionic diamond according to any one of claims 7-8, characterized in that: The application includes application of the bionic diamond in industrial fine cutting and finishing.
Citation Information
Patent Citations
Method for preparing nano polycrystalline diamond under low pressure without catalysts
CN109701447A
Polycrystalline diamond, tool provided with polycrystalline diamond, and polycrystalline diamond production method
CN111263741A
Layered carbon grain boundary phase toughened diamond multiphase material and preparation method thereof
CN114763307A
Diamond polycrystal and method for producing diamond polycrystal
CN116411346A
Ultra-high hardness nano-twin crystal diamond bulk material, and production method therefor
JP2016087481A